PENGARUH KEGIATAN MENGHIAS BAHAN SISA TERHADAP KEMAMPUAN MOTORIK HALUS PADA ANAK USIA 5-6 TAHUN DI TK AL-MUHSININ PEKANBARU - Nurul shoffariyah; Daviq Chairilsyah; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on field observations of the fine motor skills of the students is still low and teachers are still teaching methods that dominate and not varied. So that should be the implementation of the rest of the decorating material. This study aims to determine the effect of the rest of the decorating material to the fine motor skills in children aged 5-6 years in kindergarten Al-Muhsinin Pekanbaru. The sample used in this study were 15 children. The data collection techniques were used that observation. The study hypothesis fine motor skills on students after applying the rest of the decorating materials also show the results of analysis of data obtained t = 23 784 and p = 0.000. Because p ˂ 0.05 it can be concluded that there are differences in the fine motor skills in children is very significant after melakuakan decorating the residue in learning. So Ho rejected and Ha accepted which means no significant difference between before and after performing experiments by event decorating materials.. On the test of the hypothesis can be seen t = 23 784> t table = 1.761. Thus Ho rejected and Ha accepted. It can be seen from the value of P = 65.25% means the influence of the rest of the decorating material to the fine motor skills in children aged 5-6 years amounted to 65.25%